Courtly culture : literature and society in the high Middle Ages - Bumke, Joachim (University of California Press, 1991)
Well received when it was originally published in Germany in 1986, this classic study by Joachim Bumke (Univ. of Cologne) is a systematic review of the link between the literary and social culture of Germany in the 12th and 13th centuries. The focus is on the accuracy of the descriptions of festive society at court, specifically of the material culture and mannerisms, by medieval writers of epic and poetic literature. Bumke's book covers different ground with considerably greater detail than the more readable Richard J. Berleth's The Orphan Stone: The Minne singer Dream of Reich ( LJ 9/1/90), which describes the attempts by German medieval poets to influence the attitudes of their time. Addressed to readers with specialized knowledge, Bumke's book will appeal to students of German medieval literature and historians. The translation is good, though some typos are evident. Recommended for all collections of medieval literature. --Ingrid Schierling, Univ. of Colorado at Colorado Springs Copyright 1991 Reed Business Information, Inc.